MODELING OF THE UNCONFINED COMPRESSIVE STRENGTH TEST OF LIGNITE FROM PESTEANA OPENPIT MINE USING THE COMBINED FINITE-DISCRETE ELEMENT METHOD – FDEM - Alexandru Robert CIOCLU; Ionela Cristina MĂCEŞARU; Florin Dumitru POPESCU (Fiabilitate şi Durabilitate)
The property of rocks to oppose and keep their shape almost unchanged under the action of load is called strength. Compressive strength is defined as the maximum stress a material can withstand until its failure. Besides the physical characteristics of the rock, this is determined by factors such as orientation, duration and direction of the stress acting on the rock. This paper presents the simulation of a conventional Unconfined Compressive Strength (UCS) laboratory testing of a sample, with the help of Geotechnica Irazu software, based on the Finite-Discrete Element Method – FDEM.